Systematic Overview of Bacopa monnieri (L.) Wettst. Dominant Poly-Herbal Formulas in Children and Adolescents - James D Kean; Luke A Downey; Con Stough (Medicines, 2017)
Background: The Ayurvedic medicinal system employs a holistic approach to health, utilising the synergistic properties of organic resources. Research into the Ayurvedic herb Bacopa monnieri (L.) Wettst. (B.monnieri) has reported improvements in cognitive outcomes in child and adult populations. The aim of current review is to systematically assess and critically summarize clinical trials investigating B.monnieri-dominant poly-herbal formulas and their effects on the cognition, memory, learning, and behaviour in children and adolescents. Methods: Key word searches were performed using PubMed, Scopus, Cochrane Library, DHARA, and CINAHL for publications meeting inclusion criteria up to November 2017. There were no restrictions in study design. Effect sizes were calculated for all significant findings to allow for direct comparisons, and each study was evaluated on design quality. Cognitive and behavioural outcomes were grouped into validated constructs for cross-study comparison. Results: Nine trials met inclusion criteria. Five studies reported sufficient data for effect size analysis with most improvements reported in behavioural outcomes. True cognitive abilities and behavioural constructs were reviewed in six studies, with visual perception, impulsivity, and attention demonstrating the greatest improvements. The veracity of the evidence for the formulations reviewed is weakened by inconsistent statistical design and under-reporting of safety and tolerability data (44%). Conclusions: The current review extends research supporting B.monnieri as a cognitive enhancer and provides modest evidence for the use of B.monnieri in poly-herbal preparations for improving cognitive and behavioural outcomes in child and adolescent populations. Greater emphasis on statistical vigour and the reporting of tolerability data are essential for future trials to adequately document poly-herbal treatment efficacy.